Pelayanan Publik pada Lembaga Pemasyarakatan (Analisa Hukum: Peningkatan Kualitas Sistem Kunjungan di Lapas) (Lex Jurnalica, 2009)
Either one bound up prisoner rights straightforward with public service is accept family visit, jurisdictional counselor, or another particular person. Each it unmitigated prisoner is social being that does ever have the will for associate and gets socialization with society / its community, particularly with indispensable person (family, jurisdictional counselor, associate, churchman, and other as it). Therefore, each prisoner as part of society (public) one that have problem with jurisdictional, regular shall get its rights rights as it were ruled by rule legislation which applies. One of belonging of prisoner and socializing protege terminological PP's rule Number 28 Years 2006 about changes on PP Number 32 Years 1999 about Requisite and Rights performing Procedures WBP IS accept family visits, jurisdictional counselor or person another particular. Right for this prisoner rights at other side constitutes to do bit for Lapas, as one of shaped ministering public of promoter institution state that its activity funded by APBN.Â Keywords: Public Service, Right For Prisoners, Â Law AnalysisÂ